Online hierarchical and distributed method for voltage control in distribution smart grids - Fallahzadeh-Abarghouei, Hossein; Nayeripour, Majid; Hasanvand, Saeed; Waffenschmidt, Eberhard (IET generation, transmission & distribution, 2017)
This study proposes a coordinated and distributed smart grid based method for optimal set points of distributed generators (DGs) as well as on-load tap changer (OLTC) transformer in the unbalanced power distribution grid. In this approach, energy efficiency is improved and voltage profile is kept in an acceptable range under different operating conditions of renewable energy resources and loads. In the first level of proposed hierarchical method, DGs are independently trying to keep voltage profile in an acceptable range in an optimal way. If the first level is not succeeding, at the second level, OLTC cooperates with the first level to eliminate the voltage violation in the system. The rules for updating control setting are derived based on distributed gradient algorithm. The proposed distributed solution presents analogous steady state results in comparison with centralised optimisation solution. Since the processing data is reduced, short-timed response to change operating conditions could be achieved. Simulation results on three distribution test systems with different sizes demonstrate the effectiveness of proposed control solution.